PENGARUH MENGGUNAKAN GAMBAR-GAMBAR TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPTIF PADA SISWA TAHUN KEDUA DI MTs HUBBUL WATHAN RIMBA MELINTANG ROKAN HILIR - Nadia, Mutiara; Eliwarti, Eliwarti; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed to find out whether there is a significant effect of using pictures in writing descriptive text at the second year students of MTs Hubbul Wathan Rimba Melintang Rokan Hilir in the Academic Year 2018/2019 This is a pre-experimental research conducted by using a pre-test, treatment, and post-test. The instrument used in this research was tests (pre-test and post-test) which contain writing activities in describing pictures. The population of this research were the Second Year Students of MTs Hubbul Wathan Rimba Melintang Rokan Hilir. The sample of the research was the VIII A as big as 31 students. The needed data were collected by giving the writing test about descriptive text (pre-test and post-test) to the students. The collected data were analyzed by using t-test formula. The results of data analysis showed that the mean score of pretest was 35.05, and the mean score of posttest was 38.92 and the difference between the two mean score was 3.87. Besides that, t-test of this research was -11.774 and t-table of this research was 2.042. It means that the t-test score is higher than t-table (-11.774>2.042). It can be concluded that there is a significant effect of using Pictures on the ability in writing descriptive texts of the second year students at MTs Hubbul Wathan Rimba melintang Rohil. In other words, the alternative hypothesis of this research was accepted. Thus, the use of pictures improves students writing ability especially in writing descriptive texts as media.Key Words: Pictures, Writing ability, Descriptive Text